Deleted in Malignant Brain Tumors 1 (DMBT1) is present in hyaline membranes and modulates surface tension of surfactant - Müller, Hanna (BioMed Central, 2007)
BACKGROUND: Deleted in Malignant Brain Tumors 1 (DMBT1) is a secreted scavenger receptor cysteine-rich protein that binds various bacteria and is thought to participate in innate pulmonary host defense. We hypothesized that pulmonary DMBT1 could contribute to respiratory distress syndrome in neonates by modulating surfactant function. METHODS: DMBT1 expression was studied by immunohistochemistry and mRNA in situ hybridization in post-mortem lungs of preterm and full-term neonates with pulmonary hyaline membranes. The effect of human recombinant DMBT1 on the function of bovine and porcine surfactant was measured by a capillary surfactometer. DMBT1-levels in tracheal aspirates of ventilated preterm and term infants were determined by ELISA. RESULTS: Pulmonary DMBT1 was localized in hyaline membranes during respiratory distress syndrome. In vitro addition of human recombinant DMBT1 to the surfactants increased surface tension in a dose-dependent manner. The DMBT1-mediated effect was reverted by the addition of calcium depending on the surfactant preparation. CONCLUSION: Our data showed pulmonary DMBT1 expression in hyaline membranes during respiratory distress syndrome and demonstrated that DMBT1 increases lung surface tension in vitro. This raises the possibility that DMBT1 could antagonize surfactant supplementation in respiratory distress syndrome and could represent a candidate target molecule for therapeutic intervention in neonatal lung disease.